Project Report on AT89C51 Controller 28c64 Burner based on RS232 Interface - INDRANIL DASGUPTA, MILIND MADAN, PALGUN A R and DEBOJYOTI ROY (2004)
INTERNAL GUIDE: R KUMAR, MVJCE EXTERNAL GUIDE: MADHULAR SAH, UNITED TELECOM
Keywords: RS232 Interface